2018
DOI: 10.1080/23809000.2018.1483193
|View full text |Cite
|
Sign up to set email alerts
|

Cancer symptom response as an oncology clinical trial end point

Abstract: Introduction: A critical challenge in oncology is interpreting clinical trial results to inform clinical decision making. Clinical trials typically focus on overall survival (OS) and progression-free survival (PFS) as primary endpoints, which do not reflect early signs of meaningful patient benefit or harm. Cancer symptom response (CSR) can provide information about early treatment response, and studies show that CSR predicts long-term health outcomes. Areas covered: CSR requires careful consideration of its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…This suggests that assessment of symptom burden prior to treatment initiation contributes clinically useful prognostic information for treatment decision-making among older adults. Because of the expected limited survival in this population, baseline symptom burden could be more clinically meaningful for estimating outcomes than the response to treatment, the traditional oncology clinical trial end point …”
Section: Discussionmentioning
confidence: 99%
“…This suggests that assessment of symptom burden prior to treatment initiation contributes clinically useful prognostic information for treatment decision-making among older adults. Because of the expected limited survival in this population, baseline symptom burden could be more clinically meaningful for estimating outcomes than the response to treatment, the traditional oncology clinical trial end point …”
Section: Discussionmentioning
confidence: 99%
“… 15 The experimental medicines used in CCTs can create life-restricting fatigue, sickness or retching, and other adverse effects. 16 Moreover, cancer itself can cause neuropathies, pain, and psychological distress, among other events. 16 , 17 However, we found that perceived benefits of research participation were important to all patients and were a factor in trial retention, even in the face of many perceived burdens.…”
Section: Discussionmentioning
confidence: 99%
“…PROs are defined as "any report of the status of a patient's (or person's) health condition, health behavior, or experience with healthcare that comes directly from the patient, without interpretation of the patient's response by a clinician or anyone else" [17] . In clinical trials, PROs enhance understanding of treatment toxicity, HRQOL, and treatment value [18][19][20][21][22] . In clinical practice, PROs aid early symptom detection, symptom management, and treatment decision making [23][24][25][26][27] .…”
Section: Patient-reported Outcome Assessment In Immunotherapymentioning
confidence: 99%